Child Development in Primary Schools: Educational Management Implications for Student Achievement and Wellbeing - Muhammad Aldi; Retisfa Khairanis (Jurnal Ilmu Pendidikan Dasar Indonesia, 2025)
This research shows that child development in primary school is a very important aspect in determining long-term educational success. This study aims to analyze how education management in primary schools contributes to students' academic achievement and well-being This study combined quantitative surveys and qualitative interviews to explore the impact of educational management on elementary students’ academic performance and well-being. Data was collected from State Elementary School 01 Dadaprejo Batu city and rural areas with 50 students and 20 teachers as respondents. The results showed that good education management, including flexible curriculum planning, parental involvement, and a conducive learning environment, had a positive correlation with improved student academic performance. In addition, emotional support from teachers and the implementation of innovative learning strategies contribute significantly to students' psychological well-being. The implications of this study emphasize the importance of strengthening school management policies that are orientated towards the holistic development of children. The contribution of this research is expected to serve as a reference for policymakers in designing more adaptive and inclusive educational strategies to support students' academic development and well-being in primary schools.